Thienemannimyia Fittkau (Diptera: Chironomidae) from China - Cheng, Ming; Wang, Xinhua (Zootaxa, 2009)
The genus Thienemannimyia Fittkau, 1957 is recorded from the Oriental region for the first time. T. barberi (Coquillett, 1902), T. fusciceps (Edwards, 1929) and T. laeta (Meigen, 1818) are reported in the region, and two new species, T. dimorpha sp. n. and T. galbina sp. n. are described and illustrated as males. T. fusciceps and T. geijskesi (Goetghebuer, 1934) are also recorded from Palaearctic China. The generic diagnosis is emended and a key to the males of Thienemannimyia is presented.